Effect of Different Combinations of Nutrient Sources and Weeding Practice on the Physiological Characters of Rapeseed in Humid Subtropical Condition of Chitwan - Basnet, KB (Journal of the Institute of Agriculture and Animal Science, 2005)
A field experiment was conducted during the winter season of 2001-2002 at Mangalpur, Chitwan, Nepal to evaluate the performance of rapeseed in different agronomic management practices. The experiment was conducted with 16 treatments in a randomized complete block design (RCBD) with three replications. The treatments included control without input and four agronomic inputs (NPK, FYM, micronutrient- Zn, B and S and weeding), six and four combinations of two and three inputs respectively and a full package with all inputs. Application of NPK fertilizers increased leaf area and total dry matter per plant significantly as compared to control and weeding practice at 55 and 40 DAS, respectively. Further, in two factor combinations, significantly higher leaf area and particularly total dry matter per plant was produced by the application of NPK fertilizers with FYM at all stages (25 to 85 DAS) of growth and development. Finally, exclusion of NPK fertilizers in the combination of three agronomic inputs significantly lowered leaf area and total dry matter per plant as compared to others which included it at 40 and 70 DAS. All above mentioned trends were reflected on rapeseed yield indicating its significant correlation with leaf area (r=0.971) and total dry matter per plant (r=0.976). In general, addition of NPK fertilizers to other combinations of agronomic inputs increased leaf area and total dry matter per plant significantly. Key words: Leaf area, dry matter, agronomic inputs, yieldJ. Inst. Agric. Anim. Sci. 26:51-55 (2005)